Filsafat Pendidikan Ki Hajar Dewantara sebagai Landasan Pendidikan Vokasi di Era Kurikulum Merdeka - Deasy Irawati; Siti Masitoh; Mochamad Nursalim (JUPE : Jurnal Pendidikan Mandala, 2022)
The Merdeka Curriculum tries to restore the paradigm of Indonesian education in accordance with Ki Hajar Dewantara's Educational Philosophy. Ki Hajar Dewantara's educational philosophy which upholds meeting the needs of students as the main goal of education. Fulfilling students' needs by optimizing their potential through the pamong and among systems is based on the motto Ing Ngarso Sung Tulodho, Ing Madya Mbangun Karso, Tut Wuri Handayani. These three mottoes will later be implemented in the Pamong and Among systems in Student Centered-based learning so that later there will be harmony between creativity, sense of initiative and character. The implementation of Ki Hajar Dewantara's educational philosophy is evident in the learning outcomes in vocational education in general subject matters and vocational subject matters. It is clear that the government's efforts to prepare students to become future generations are ready to compete in the coming era.